USEFUL MARKETING TOOLS OF BRAND- AND PR-MANAGEMENT TO INCREASE THE COMPETITIVENESS OF ENTERPRISES IN THE HOTEL AND RESTAURANT INDUSTRY - Betlej, A.; Kaziuka, N.; Bielan, O.; Humeniuk, V. (The actual problems of regional economy development, 2024)
The article researches the theoretical aspects of brand- and PR-management of enterprises in the hotel and restaurant industry as one of the tools for increasing the competitiveness of tourist enterprises. The authors singled out such main characteristics of the brand as brand awareness, brand identity, brand penetration, brand associations, brand loyalty, and others; determined the theoretical aspects of the formation and functioning of branding, PR management and marketing communications in the hotel and tourism business in general. Research has shown that brand management and PR management are the most effective means of market promotion of services that contribute to increasing the profitability and volume of sales of goods or services, expanding the range and knowledge of consumers about their uniqueness and specialness. It has been proven that the effectiveness of branding management includes the formation, adjustment, strengthening and activation of the development of relationships between potential buyers of the product and the brand due to the creation and actualization of its individual, functional, social and communicative characteristics, as well as ensuring the recognition and identification of the trademark due to the management of its constituent components (graphics, colors, sounds, logo, advertising slogan and name). The concept of "brand" is identified as a system of combined elements that summarize the opinions, positions and perceptions of consumers about a certain product or service, organization or person. At the same time, the process of brand management is provided through the creation of a brand concept, its formation and promotion to the market thanks to branding. Five main stages (phases) within brand management are defined, the most important of which is the formation of a brand vision, because it is this stage that combines the development of the name and advertising slogan or slogan of a service or product, identification of the most basic means and tools of its promotion on the market, as well as the formation of a brand portrait, which is reproduced through the creation and strengthening of a positive image of the product in the perception of existing and potential customers and society in general. The components of the brand were determined, the factors of branding formation were considered, the "brand pyramid" was formed, and the brand management scheme was built. The task of PR is singled out as one of the functions of management.